2019
DOI: 10.1177/1934578x1901400120
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Essential Oil fromPiper jacquemontianumfrom Eight Provenances of Guatemala

Abstract: Piper jacquemontianum Kunth (Piperaceae) is a native species from Central America and the Caribbean lowlands. It is traditionally used as a medicine and condiment in several ethnic groups from the region. Essential oils of dry leaves were obtained from eight ecologically different sites of Guatemala, which were cultivated under similar conditions in the Pacific basin. The essential oil yields obtained by hydrodistillation varied with the site of collection (0.3-1.7%). The essential oil composition was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Chemical study of this species has been mainly performed on essential oils. Linalool and E -nerolidol were reported as the major constituents of its essential oil [ 29 , 30 ], whereas a recent study revealed that the composition was variable and only E -nerolidol was detected as a common constituent among the eight cultivars from different places in Guatemala [ 31 ]. Although linalool has been reported to show anti-trypanosomal activity [ 32 ], nothing has been reported on anti-trypanosomal constituents of the MeOH extract of this species.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical study of this species has been mainly performed on essential oils. Linalool and E -nerolidol were reported as the major constituents of its essential oil [ 29 , 30 ], whereas a recent study revealed that the composition was variable and only E -nerolidol was detected as a common constituent among the eight cultivars from different places in Guatemala [ 31 ]. Although linalool has been reported to show anti-trypanosomal activity [ 32 ], nothing has been reported on anti-trypanosomal constituents of the MeOH extract of this species.…”
Section: Resultsmentioning
confidence: 99%
“…17 The presence of functional groups such as "hydroxyl" in linalool, terpien-4-ol and trans-cadinol, "alkanoate" in 2-methylphenyl formate and ascorbic acid 2,6 dihexadecanoate and "ether" in safrole could contribute to the biological activities reported in this study. 30,31 The antioxidants activities of ripe and unripe pepper fruits essential oils in this study as typified by their ferric reducing antioxidant power (FRAP), Fe 2+ chelating, ABTS and DPPH radicals scavenging activities. The ferric reducing antioxidant property presented as ascorbic acid equivalent revealed that unripe pepper fruits essential oil (16.33 ± 0.30 mgAAE/g) was significantly (p < 0.05) different from ripe pepper fruit essential oil (12.55 ± 0.45 mgAAE/g) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Piper L. species are rich in essential oils (EOs), a mixture of volatile compounds usually extracted by hydrodistillation, mainly composed of terpenes and phenylpropanoids, which vary greatly according to the species, geographic location and seasonal variation [4–6] …”
Section: Introductionmentioning
confidence: 99%